Radiofrequency ablation as a method of choice for the treatment of lower extremity varicose veins disease - O. Yu. Atamaniuk; V. D. Skrypko; V. M. Atamaniuk (Сучасні медичні технології)
The aim of the work is to improve the radiofrequency ablation (RFA) protocol in order to minimize disease recurrence and to improve the life quality of patients with lower extremity varicose veins disease (LEVVD).